Biochemical and Clinical Assessments of Segmental Maxillary Posterior Tooth Intrusion - Jintana Tasanapanont; Tanapan Wattanachai; Janya Apisariyakul; Peraphan Pothacharoen; Siriwan Ongchai; Prachya Kongtawelert; Marit Midtbø; Dhirawat Jotikasthira (International Journal of Dentistry)
Objective. To compare chondroitin sulphate (CS) levels around maxillary second premolars, first molars, and second molars between the unloaded and the loaded periods and to measure the rates of intrusion of maxillary posterior teeth during segmental posterior tooth intrusion. Materials and Methods. In this prospective clinical study, 105 teeth (from 15 patients exhibiting anterior open bite and requiring maxillary posterior tooth intrusion) were studied. Competitive ELISA was used to detect CS levels. Dental casts (during the unloaded and loaded periods) were scanned, and posterior tooth intrusion distances were measured. Results. During the unloaded period, the median CS levels around maxillary second premolars, first molars, second molars (experimental teeth), and mandibular first molars (negative control) were 0.006, 0.055, 0.056, and 0.012 and during the loaded period were 2.592, 5.738, 4.727, and 0.163 ng/μg of total protein, respectively. The median CS levels around experimental teeth were significantly elevated during the loaded period. The mean rates of maxillary second premolar and first and second molar intrusion were 0.72, 0.58, and 0.40 mm/12 weeks, respectively. Conclusions. Biochemical and clinical assessments suggested that the segmental posterior tooth intrusion treatment modality with 50 g of vertical force per side was sufficient. Trial Registration. The study is registered as TCTR20170206006.